A Cross Sectional Study to Assess the Knowledge, Attitude and Practice on Personal Hygiene among School Children in Rural Primary School of Kheda District, Gujarat - Kailash Nagar; Jyot Darji; Shiney Parmar; Niral Patel; Niyati Patel (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background of Study: Personal hygiene is very important in all stage of human life, but appropriate cleanliness habits should be started from childhood. Children are who learn about good hygiene practice it will be last longer the life and will carry during adulthood1. Hygiene guidance counseling should start as earliest possible along with parents so parents can teach about right hygiene to their children2.Objectives: 1. To assess the Knowledge regarding personal hygiene among primary school children. 2. To assess the Attitude regarding personal hygiene among primary school children. 3. To assess the practice regarding personal hygiene among primary school children. 4. To prepare and distribute a health education pamphlet on personal hygiene. Methodology: The Descriptive survey approach cross sectional study research design carried out for the study, Sampling method was Non Probability sampling technique Convenience sampling method Study population Primary and middle school children. (5th, 6th & 7th standard) Study Setting Rural Primary School Kheda District Study Size 100 School Children’s3.Results: Regarding the distribution of sample according to knowledge regarding hand hygiene where 3(10%) had Moderate knowledge, 27(90%) Had Adequate Knowledge and none of them had inadequate knowledge. Only 17.3 % children’s found that they does not used and cloth or tissue paper during sneezing or coughing and rest of para-meter regarding hand hygiene were founded that primary school children had good practice.